Role of Motility and Chemotaxis in Efficiency of Nodulation by Rhizobium meliloti - Caetano Anollés, Gustavo (1988)
Spontaneous mutants of Rhizobium meliloti L5-30 defective in motility or chemotaxis were isolated and compared against the parent with respect to symbiotic competence. Each of the mutants was able to generate normal nodules on the host plant alfalfa (Medicago sativa), but had slightly delayed nodule formation, diminished nodulation in the initially susceptible region of the host root, and relatively low representation in nodules following co-inoculation with equal numbers of the parent. When inoculated in growth pouches with increasing dosages of the parental strain, the number of nodules formed in the initially susceptible region of the root increased sigmoidally, with an optimum concentration of about 105 to 106 bacteria/plant. The dose-response behavior of the nonmotile and nonchemotactic mutants was similar, but they required 10- to 30-fold higher concentrations of bacteria to generate the same number of nodules. The distribution frequencies of nodules at different positions along the primary root were very similar for the mutants and parent, indicating that reduced nodulation by the mutants in dose-response experiments probably reflects reduced efficiency of nodule initiation rather than developmentally delayed nodule initiation. The number of bacteria that firmly adsorbed to the host root surface during several hours of incubation was 5- to 20-fold greater for the parent than the mutants. The mutants were also somewhat less effective than their parent as competitors in root adsorption assays. It appears that motility and chemotaxis are quantitatively important traits that facilitate the initial contact and adsorption of symbiotic rhizobia to the host root surface, increase the efficiency of nodule initiation, and increase the rate of infection development.